An application of energy and exergy analysis in agricultural sector of Malaysia - Ahamed, Jamal Uddin; Saidur, Rahman; Masjuki, Haji Hassan; Mekhilef, Saad; Ali, M.B.; Furqon, M.H. (Elsevier, 2011)
Thermodynamic losses usually take place in machineries used for agricultural activities. Therefore, it is important to identify and quantify the losses in order to devise strategies or policies to reduce them. An exergy analysis is a tool that can identify the losses occurred in any sector. In this study, an analysis has been carried out to estimate energy and exergy consumption of the agricultural sector in Malaysia. Energy and exergy efficiencies have been determined for the devices used in the agricultural sector of Malaysia, where petrol, diesel and fuel oil are used to run the machineries. Energy and exergy flow diagrams for the overall efficiencies of Malaysian agricultural sector are presented as well. The average overall energy and exergy efficiencies of this sector were found to be 22 and 20.728, respectively, within the period from 1991 to 2009. These figures were found to be lower than those of Norway but higher than Turkey.